Analisis pengaruh profesionalisme, kepuasan kerja, kepuasan tingkat kompensasi, komitmen organisasional dan motivasi terhadap turnover intentions staff auditor di kantor akuntan publik (studi pada KAP di Pekanbaru dan Batam) - Gusrianto, Calwin; Diyanto, Volta; ', Rasuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The objective of this study is to get an empirical evidence about the effects of profesionalism, job satisfaction, salaries satisfaction, organizational commitment and motivation upon the turnover intentions to auditor who work at Pekanbaru and Batam accounting firm.Data collected through questionnaires by using convenience sampling. There were 66 questionnaires distributed, 48 were returned and 43 questionnaires used for the analysis.The data analysis was done by using multiple regression. The result of this research showed that there were no significant effect of profesionalism, salaries satisfaction, and motivation as individual factor upon the turnover intentions. For job satisfaction and organizational commitment, there were negative effect upon the turnover intentions.Keywords: Profesionalism, Job Satisfaction, Salaries Satisfaction, Organizational Commitment, Motivation, Turnover Intentions.